Evaluation of Different Sampling Methods Combined with Metagenomic Next-Generation Sequencing of Respiratory Specimens in Etiological Diagnosis of Patients with Severe Pneumonia - Zhou P; Zhang D; Fu J; Zhu D; Li S (Infection and Drug Resistance, 2024)
Peng Zhou,1 Dehua Zhang,2 Jianjian Fu,3 Dongling Zhu,4 Shixiao Li5 1Department of Pharmacy, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Emergency Department, Enze Hospital, Taizhou Enze Medical Center (Group), Taizhou, Zhejiang, People’s Republic of China; 3Burn Department, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Taizhou, Zhejiang, People’s Republic of China; 4Nursing Department, Taizhou Hospital of Zhejiang Province affiliated to Wenzhou Medical University, Taizhou, Zhejiang, People’s Republic of China; 5Department of Clinical Microbiology Laboratory, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Taizhou, Zhejiang, People’s Republic of ChinaCorrespondence: Shixiao Li, Email lsx0992@126.comObjective: To evaluate the value of respiratory specimens collected via different sampling methods combined with metagenomic next-generation sequencing (mNGS) in the etiological diagnosis of severe pneumonia.Methods: A total of 117 patients with severe pneumonia between 2019 and 2024 were included in this study, with 60 patients undergoing endotracheal aspiration (ETA) and 57 undergoing bronchoalveolar lavage (BAL), respectively. Patient records were retrospectively reviewed. Both ETA and BAL samples were tested using mNGS and conventional microbiological tests (CMT) to compare the detection rates, microbial profiles and their effects on clinical outcomes.Results: The positive rates of mNGS for ETA and BAL samples were 96.7% and 80.7%, respectively, which were higher than CMT. A total of 39 pathogenic microorganisms were detected, of which Klebsiella pneumoniae, Candida albicans and herpes simplex virus-4 (HSV-4), and cytomegalovirus (CMV) were the most commonly detected as bacteria, fungi and viruses, respectively. The percentages of Pseudomonas aeruginosa (30.0% vs 12.3%, p = 0.019) and Stenotrophomonas maltophilia (25.0% vs 8.8%, p = 0.020) were significantly higher in the ETA group compared to the BALF group. The detection rate of three or more microorganisms was notably higher in the ETA group. No significant differences existed in antibiotics adjustment between the groups. The ETA group experienced a higher frequency of continuous renal replacement therapy (CRRT), mechanical ventilation and complications. There was no significant difference in the hospital length of stay, duration of mechanical ventilation and mortality between both groups.Conclusion: Respiratory specimens collected by different sampling methods yield different microbial findings. ETA and BAL combined with mNGS play a role in guiding the pathogenetic diagnosis of patients with severe pneumonia. However, it is recommended that their sampling methods be determined by clinical symptoms and patient conditions.Keywords: metagenomic next-generation sequencing, sampling method, severe pneumonia, etiological diagnosis